2017
DOI: 10.1103/physrevlett.119.206402
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Types of Topological Fermions in Transition Metal Silicides

Abstract: Exotic massless fermionic excitations with non-zero Berry flux, other than Dirac and Weyl fermions, could exist in condensed matter systems under the protection of crystalline symmetries, such as spin-1 excitations with 3-fold degeneracy and spin-3/2 Rarita-Schwinger-Weyl fermions. Herein, by using ab initio density functional theory, we show that these unconventional quasiparticles coexist with type-I and type-II Weyl fermions in a family of transition metal silicides, including CoSi, RhSi, RhGe and CoGe, whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
432
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(471 citation statements)
references
References 72 publications
21
432
2
1
Order By: Relevance
“…Finally, we mention that the three-component fermions observed in WC are essentially distinct from the chiral fermions enforced by filling and symmetry in the non-symmorphic systems 4,10,11,18 , in which the non-zero topological charges protect the Weyl-type Fermi arcs. In the latter case, the bulk nodes with opposite topological charges are pinned at either the centre or the corner of the bulk BZ, and thus the surface Fermi arcs connecting their projections can span over a wider segment of the surface BZ.…”
Section: Nature Physicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Finally, we mention that the three-component fermions observed in WC are essentially distinct from the chiral fermions enforced by filling and symmetry in the non-symmorphic systems 4,10,11,18 , in which the non-zero topological charges protect the Weyl-type Fermi arcs. In the latter case, the bulk nodes with opposite topological charges are pinned at either the centre or the corner of the bulk BZ, and thus the surface Fermi arcs connecting their projections can span over a wider segment of the surface BZ.…”
Section: Nature Physicsmentioning
confidence: 95%
“…In addition to four-and two-fold degeneracy, it has been shown that space-group symmetries in crystals may protect other types of degenerate point, near which the quasiparticle excitations are not the analogues of any elementary fermions described in the standard model. Theory has proposed three-, six-and eight-fold degenerate points at high-symmetry momenta in the BZ in several specific non-symmorphic space groups 3,4,10,11 , where the combination of nonsymmorphic symmetries and other point symmetries leads to three-, six-and eight-dimensional irreducible representations. Theory has also proposed that in a symmorphic space group P m 6 2 (no.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In principle the inclusion of broken T makes the possibilities even richer. A particularly promising family of materials that is expected to combine multiple types of band touching and long Fermi-arcs on certain surfaces may be found in the AB material class (A = Co, Rh and B=Si, Ge) (Chang et al, 2017;Tang et al, 2017).…”
Section: Kramers-weyl Nodes and "New" Fermionsmentioning
confidence: 99%
“…Exploiting these advances in symmetry and electronic structure, researchers have just recently proposed the presence of closely related topological surface states and doubled threefold fermions in readily synthesizable crystals in the RhSi family [10,11]. Given the immense number of known crystalline compounds still uninvestigated for nodal fermions, other ideal materials candidates will surely follow.…”
mentioning
confidence: 99%